GENEALOGI PEMAKNAAN TAJASSUS Q.S AL-HUJURAT/49:12 (IAIN KENDARI, 2023)
This research is about tajassu>s actions where these actions are strictly prohibited by Allah but nowadays these actions are used as a tool in defending an area or a threat that is certain to occur. So that this study aims to find out how the genealogy of the meaning of tajassu>s in classical, modern and contemporary interpretations in Q.s al-Hujura/49:12. In this case, we want to know how changes have occurred in the meaning of tajassu>s from the time of the Prophet to today's modern times. This research is a literature review or library research. The approach used in this study is an interpretive approach. the primary data used was Q.s al-Hujurat/49:12, while the secondary data used included commentary books, hadith books and articles related to the research title. While the data collection technique is collecting data from various existing references regarding this research, then analyzing the data with descriptive analysis. In analyzing the data using contextual interpretation, intertextual. From the results of this study it was discovered how the meaning of tajassu>s that occurs from classic, modern and contemporary commentary books, namely the act of tajassu>s will change its meaning in various circumstances and times. At the time of the Prophet, the act of tajassu>s was strictly prohibited because the prohibition was very clearly explained in the Koran. However, nowadays tajassu>s or now known as espionage or intelligence has become a tool that aims to prevent danger or to avoid threats that will occur. In the current espionage process, espionage or intelligence agents are sometimes used to directly search for information, but with the development of the era, espionage is also carried out using technological tools, such as wiretapping by telephone or by CCTV.